Analisis Faktor-faktor Yang Berpengaruh Terhadap Cash Dividend Pada Perusahaan Go Publik Di Bursa Efek Indonesia - Yuliani . (Universitas Kristen Maranatha, 2009)
This research was to analyzed the factors influencing cash dividend on Indonesian Stock Exchange (IDX) during 2003-2007 observation period. Samples used purposive on LQ-45 with a criteria during observation period, the emiten divide dividend, so that the total samples obtained 13, and, after the process of Clasik Assumption is done, it reached 31 observations. Data Analysis technique used multiple regression analysis with Ordinary Least Square (OLS). Funding shown that DTA, EPS, and CFFF had significantly influenced cash dividend. On the other side, ROI, CaR, CR, CF, CFFO and CFFI was not significant. Simultaneously, independent variables were proved that they influenced on Cash Dividend.Keywords: Return on Investment, Cash Ratio, Current Ratio, Debt to Total Asset, Earning Per Share, Cash Flow From Operation, Cash Flow From Investing, Cash Flow From Financing, Cash Dividend.